A fuzzy-based occupational health and safety risk assessment framework and a case study in an international port authority. Issue 4 (18th November 2020) - Gul, Muhammet
Abstract : Ports are complex systems that play a crucial role in the transportation of maritime-related products and services. Since ports face various safety issues in design, installation, operation and maintenance processes, there are many aspects open for improvement in Occupational Health and Safety risk assessment and it is required to deal with risks, reduce them to an acceptable level and control. To struggle with emerging risks and manage this process better, a risk assessment framework is proposed for ports in this study. A case study is performed in a Turkish international port authority using the proposed framework. Fuzzy Analytic Hierarchy Process (FAHP), which is a commonly used fuzzy multi-criteria decision-making method, was used in weighting two risk factors: likelihood and severity . The orders of priority of hazards were then determined by a fuzzy-based VIKOR method based on the output of FAHP. The proposed framework overcomes some drawbacks, including a lack of assignment on the weight to two risk assessment factors and lack of the high dependence of the prioritisation on the experts' opinions. To validate the results, a sensitivity analysis was conducted. In conclusion, the study contributes to the applicability of the proposed framework to assess the risks in ports and provides a distinct risk prioritisation.